2022
DOI: 10.1038/s41598-022-15526-7
|View full text |Cite
|
Sign up to set email alerts
|

iCodon customizes gene expression based on the codon composition

Abstract: Messenger RNA (mRNA) stability substantially impacts steady-state gene expression levels in a cell. mRNA stability is strongly affected by codon composition in a translation-dependent manner across species, through a mechanism termed codon optimality. We have developed iCodon (www.iCodon.org), an algorithm for customizing mRNA expression through the introduction of synonymous codon substitutions into the coding sequence. iCodon is optimized for four vertebrate transcriptomes: mouse, human, frog, and fish. User… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 65 publications
0
25
0
Order By: Relevance
“…The Trichoplax adhaerens AKDF 19383 sequence was established by additional genome annotation of the Genbank TRIADDRAFT_19383 sequence (described in Fig. S4 legend), codon-optimized for Xenopus laevis in iCodon 69 , and commercially synthesized and cloned into a modified pSP64-poly(A) vector (full sequence in Supplemental text).…”
Section: Plasmids and Molecular Biologymentioning
confidence: 99%
“…The Trichoplax adhaerens AKDF 19383 sequence was established by additional genome annotation of the Genbank TRIADDRAFT_19383 sequence (described in Fig. S4 legend), codon-optimized for Xenopus laevis in iCodon 69 , and commercially synthesized and cloned into a modified pSP64-poly(A) vector (full sequence in Supplemental text).…”
Section: Plasmids and Molecular Biologymentioning
confidence: 99%
“…For mRNA production, vectors were linearized with NotI (NEB) and in vitro transcribed using mMessage mMachine SP6 kit (Ambion). A DNA fragment for mScarlet-i3 46 was codon-optimized using iCodon 57 , purchased from IDT as GBlocks and cloned into pCS2+ NbALFA as described above. pCS2+mNeonGreen-C Cloning Vector was a gift from Ken-Ichi Takemaru (http://n2t.net/addgene:128144; RRID:Addgene_128144 Degron GEAR adapters and degron reporters Zebrafish fbxw11b ORF was amplified from pCS2+ zGrad (Addgene plasmid # 119716) and cloned into pCS2+ GEAR binder clones to replace EGFP ORF using InFusion enzyme (Takara).…”
Section: Molecular Cloningmentioning
confidence: 99%
“…The mRNA stability of the zebrafish genes was predicted from the protein-coding sequences using iCodon algorithm [69]. Only sequences with a length multiple of three were used for the analysis.…”
Section: Mrna Stability Prediction By Icodonmentioning
confidence: 99%
“…In addition to nascent peptides held in ribosomes, codon sequences also affect the ribosome traversal [68]. Interestingly, genome-wide prediction of mRNA stability by iCodon, which accounts for the effect of codons on mRNA stability, revealed that mRNAs encoding zinc finger transcription factors are significantly unstable in humans [69]. Moreover, iCodon predicted that zebrafish C2H2-ZF genes were significantly unstable, and C2H2-ZF genes upregulated in MZznf598 were predicted to be even less stable (Supplemental Figure 5I).…”
Section: Sequence Features That Induce Ribosome Stalling At C2h2-zfmentioning
confidence: 99%